2000
DOI: 10.1007/bf02494778
|View full text |Cite
|
Sign up to set email alerts
|

Condensation of 2-hydroxyacetophenones with trichloroacetonitrile as a route to 2-trichloromethylchromones and 4-hydroxycoumarins

Abstract: Condensation of 2-hydroxyacetophenones with [richloroacetonitrile in the presence of Nmethylanilinomagnesium bromide affords hydroxyary'l [}-amino-l~-trichloromethylvinyl ketones, which are converted into 2-trichloromethylchromones upon treatment with concentrated HCI. rite restllting compounds react with alcoholic solutions of NH-, or KOH to form 3-amino-I-( 2-hydrowaryl)-4,4,4-trichlorobut-2-en-f -ones and 4-hydroxycoumarins, respecti,~elv.Key ~ords: 2-hydroxyacetophenones, trichloroacetonitrile, 3-amino-1-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The oxidation reaction of compound 6 with selenium dioxide in dry dioxane yielded bis{chromeno [4,3-c]pyrazol-4-oxo-2-yl}phosphine oxide (7) (Scheme 7). The absorption band of carbonyl groupappeared at 1652 cm -1 [34,35] in the IR spectrum of 7. Also, its structure was confirmed from 1 H NMR spectrum by disappearance of OH and C2-H protons of compound 6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation reaction of compound 6 with selenium dioxide in dry dioxane yielded bis{chromeno [4,3-c]pyrazol-4-oxo-2-yl}phosphine oxide (7) (Scheme 7). The absorption band of carbonyl groupappeared at 1652 cm -1 [34,35] in the IR spectrum of 7. Also, its structure was confirmed from 1 H NMR spectrum by disappearance of OH and C2-H protons of compound 6.…”
Section: Methodsmentioning
confidence: 99%
“…Abdel-Aziz et al / European Journal of Chemistry 2 (1) (2011)[25][26][27][28][29][30][31][32][33][34][35] …”
mentioning
confidence: 99%
“…The required 4‐phenylaminocoumarin derivatives 3a–c (R= H, 8Me, and 6Cl, respectively) were synthesized by reaction of aniline with the corresponding 4‐hydroxycoumarins ( 2a–c , R= H, 8Me, and 6Cl, respectively), under microwave irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…1 We showed that these compounds can be obtained by the condensation of 2-hydroxyacetophenones with trichloroacetonitrile in the presence of N-methylanilinomagnesium bromide followed by acid hydrolysis of the aminoenones. [2][3][4][5] In several cases, formation of aminoenones was accompanied by considerable polymerization of the reaction mixture, impeding the isolation of target products. Till date, this reaction was the only method for obtaining 2-trichloromethylchromones in moderate yields because the Claisen condensation usually used for synthesis of chromones gives unsatisfactory results in the case of trichloroacetic acid esters due to side reactions associated with haloformic splitting 6 and formation of dichlorocarbene.…”
mentioning
confidence: 99%